Trends in educational policies related to educational quality: a systematic review - Azaña Lucio, Pablo Sebastian (2024)
Introduction: The purpose of this systematic review study was to analyze current trends in educational policies related to educational quality in Spanish-speaking countries. Methods: The study involved an exploratory-descriptive and critical investigation, covering relevant articles and theses. The PRISMA method was used to conduct a systematic review, consulting priority databases such as Scopus, Science Direct, Scielo, ProQuest, Repository UCV, and Dialnet. Results: The review indicates the coexistence of various educational policy trends, including the defense of different economic systems, the pursuit of higher educational quality, the promotion of inclusivity in education, and the safeguarding of the right to education for all. These policies reflect a multifaceted approach to improving education, adapted to the specific contexts of each country. Conclusions: It is crucial to implement contextually adapted and evidence-based educational policies and to foster collaboration among stakeholders to achieve inclusive and quality education. This study contributes to understanding trends in educational policies and offers recommendations for future research and the formulation of effective policies.